Relationship Between Forms of Aggression and Social Status in South Korean Primary School Peer Groups. - Park, Jonghyo; Kim, Jingu (Journal of Child & Family Studies, 2019)
Objectives: This research aimed to explore the relationship between aggression and social status. More specifically, we differentiated between relational aggression and overt aggression, and between perceived popularity and social preference. We also considered classroom structure (i.e., density, hierarchy) a moderator in the relationship between aggression and social status. Methods: A total of 1,404 students (719 boys, 685 girls; 3rd to 6th graders) from 71 classrooms in primary schools of South Korea participated and responded via online surveys that included peer nomination of aggression and social status subtypes. Results: Multi-level analyses revealed that the negative association between relational aggression and later perceived popularity was stronger in classrooms with low density compared to ones with high density. Overt aggression enhanced social preference in hierarchical classrooms whereas it has negative association with later social preference in egalitarian classrooms. Conclusion: The results suggest that classroom structures play a significant role in reinforcing social status via specific forms of aggression. Classroom context plays a key role in this connection, as students choose their specific forms of aggression in accordance with their goals. Limitations of the study and directions for future research were suggested.